2022
DOI: 10.1002/anie.202207600
|View full text |Cite
|
Sign up to set email alerts
|

Modulating Tit2gOrbital Occupancy in a Cu/TiO2Composite for Selective Photocatalytic CO2Reduction to CO

Abstract: The electronic structure of composites plays a critical role in photocatalytic conversion, whereas it is challenging to modulate the orbital for an efficient catalyst. Herein, we regulated the t 2g orbital occupancy state of Ti to realize efficient CO 2 conversion by adjusting the amount of photo-deposited Cu in the Cu/ TiO 2 composite. For the optimal sample, considerable electrons transfer from the Cu d orbital to the Ti t 2g orbital, as proven by X-ray absorption spectroscopy. The Raman spectra results also… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
50
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 67 publications
(53 citation statements)
references
References 61 publications
3
50
0
Order By: Relevance
“…[22,23] This indicates the Co(bpy) 3 2+ /CoS@CdZnS-DETA system is thermodynamically favorable for the CO 2 conversion reaction. Afterword, protonation of COOH * to produce CO * requires a very low free energy barrier change of 0.05 eV, [44] which may explain the sole production of CO in the CO 2 reduction reaction. The downhill free energy profile suggests that the conversion from CO * to CO is easier and more spontaneous assisted with acquisition of the light-induced electron.…”
Section: +mentioning
confidence: 99%
“…[22,23] This indicates the Co(bpy) 3 2+ /CoS@CdZnS-DETA system is thermodynamically favorable for the CO 2 conversion reaction. Afterword, protonation of COOH * to produce CO * requires a very low free energy barrier change of 0.05 eV, [44] which may explain the sole production of CO in the CO 2 reduction reaction. The downhill free energy profile suggests that the conversion from CO * to CO is easier and more spontaneous assisted with acquisition of the light-induced electron.…”
Section: +mentioning
confidence: 99%
“…This is possibly due to the nonradiative quenching that was enhanced by the protonated N, demonstrating that the photogenerated charge recombination is inhibited to a certain extent in the Cu6-NH cluster. 12 Likewise, it could be observed that the tailing of the fluorescence lifetime curve of Cu6-NH became more pronounced compared with that for Cu6-N, as shown in Supplementary Fig. 29.…”
Section: Resultsmentioning
confidence: 79%
“…[4][5][6][7] Unlike the widely reported systems that require additional noble-metal-based photosensitizers and/or electron donors of organic bases, the key challenge with the artificial system lies mainly in the design of a single-component photocatalyst with suitable band structures and catalytic active centers for directly converting CO2 and H2O under solar energy, similar to the case in natural photosynthesis. [8][9][10][11] Thus far, researchers have mainly employed inorganic materials and organic conjugated polymers, such as TiO2, 12,13 ZnIn2S4, 14,15 and g-C3N4, 16,17 for the development of photocatalytic semiconductors. Few single-component photocatalysts are capable of realizing effective and highly selectively CO2 photoreduction.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…From the Tauc plot, the Eg values of the MOFs were determined to be 2.62 and 2.69 eV, which are favorable for the transition of photogenerated charge during photocatalysis. [ 42 45 ] In order to determine the exact valence band (VB) and conduction band (CB) positions of BPAN ‐Co‐ 1 and BPAN ‐Co‐ 2, the valence band X‐ray photoelectron spectra (VB‐XPS) were acquired as shown in Figure 2c,d. The VB potentials of BPAN ‐Co‐ 1 and BPAN ‐Co‐ 2, determined by the tangent intercept of the state density at the Fermi edge, were 1.15 and 0.88 eV, respectively.…”
Section: Resultsmentioning
confidence: 99%